Framing fragile and stable states through war metaphors in divisive narratives - Al Tameemi, Muaataz Riyadh Khalil; Ramesh Nair,; Dass, Laura Christ (Penerbit Universiti Kebangsaan Malaysia, 2024)
The United Nations and its specialised agencies are incentivised to use bias-free language by a fundamental human rights law which prohibits discrimination of any kind. However, it is also true that these organisations are often accused of taking sides despite wanting to remain impartial in times of crisis. While accusations of bias may be greater during conflicts between member states, this paper reveals that hegemonic discourse is also apparent in reports unrelated to conflicts and published by the World Health Organisation (WHO), a specialised agent of the United Nations. This study examines war metaphors in WHO reports, focusing on how language constructs, and perpetuates the identities of stable and fragile states. Drawing on two specialised corpora, and using a concordance software, metaphorical expressions of war were analysed within their contextual environment to investigate the use of purposeful and ideological metaphors in global health narratives. The examination of metaphorical expressions revealed that fragile states were depicted as vulnerable and dependent, reinforcing stereotypes of instability. Conversely, the same metaphors framed stable states as competent leaders and global saviours. These polarised representations contribute to legitimising existing global hierarchies and power disparities. The results offer insights into the manipulative use of nuanced language in seemingly objective reports which in turn serve to maintain the constructed realities of stable and fragile states. By exposing bias in WHO reports, the research advocates for greater accountability and transparency in global health communication. These findings provide valuable insights into the intersection of language, power, and global health governance.